ANALISIS LITERASI KEUANGAN DI KALANGAN GENERASI Z TERKAIT PRODUK PERBANKAN SYARIAH (STUDI KASUS DI KECAMATAN PADANG GELUGUR, KABUPATEN PASAMAN) - Welvy Fenancy; Sandra Dewi (CV. Adiba Aisha Amira, 2025)
Financial literacy is an important aspect in individual financial management, especially for Generation Z who are starting to enter the world of work and computers on various financial products, including Islamic banking. However, their level of understanding of Islamic banking products is still relatively low. Therefore, this study aims to analyze the factors that influence the financial literacy of Generation Z in understanding and using Islamic banking products using the Theory of Planned Behavior (TPB) approach. This study uses a qualitative method with in- depth interview techniques with informants who are members of Generation Z in Padang Gelugur District. The data obtained were analyzed using thematic analysis for understanding and the main factors that influence financial literacy. The results of the study show that attitudes, subjective norms, and behavioral control influence their understanding of Islamic banking. Financial experience and education play a role in forming positive attitudes, while social norms such as the influence of friends and the environment also play a role. However, the lack of access to information is a major obstacle. This study is expected to provide insight for Islamic banking in designing educational strategies to improve financial literacy among Generation Z.